2018
DOI: 10.1016/j.jenvman.2018.03.109
|View full text |Cite
|
Sign up to set email alerts
|

Extending the SLEUTH model to integrate habitat quality into urban growth simulation

Abstract: This study aims to support sustainable urban and environmental planning by using urban growth simulation models, in which environmental quality is employed as one of the inputs. We proposed an extended SLEUTH urban growth model (UGM) for the regions threatened by environmental quality degradation caused by uncontrolled urban expansion. In this model, habitat quality is assessed by the InVEST model and is used to represent environmental quality, which is utilized in urban growth simulation. The habitat quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(61 citation statements)
references
References 50 publications
1
60
0
Order By: Relevance
“…In addition, the degradation degree around the watershed has been increasing, especially the area with a low degradation in the Taihu Lake has been shrinking significantly, which indicated that the impact of human activities on the watershed has been deepening. These findings supported the previous studies that demonstrated that urbanization has had a significant and extensive impact on the local biodiversity [36,62].…”
Section: Habitat Degradation Change Associated With Luccsupporting
confidence: 92%
“…In addition, the degradation degree around the watershed has been increasing, especially the area with a low degradation in the Taihu Lake has been shrinking significantly, which indicated that the impact of human activities on the watershed has been deepening. These findings supported the previous studies that demonstrated that urbanization has had a significant and extensive impact on the local biodiversity [36,62].…”
Section: Habitat Degradation Change Associated With Luccsupporting
confidence: 92%
“…The relative pressure to build upon steeper slopes is dynamic and related to the proportion of flat land available and the steeper area's proximity to an already established settlement (Clarke et al, 1997;Silva & Clarke, 2002). A recent successful application used a modified slope layer to understand the effect of uncontrolled urban growth in developing regions on environmental degradation (Li et al, 2018). The study used habitat quality information from the InVEST model to replace slope and assess the impact of urbanization.…”
Section: Sleuth Model For Urban Simulationmentioning
confidence: 99%
“…In experiment 2, the slope-related coefficients were replaced by urban attraction values during calibration (Li et al, 2018). The model's default value of 0.1 was used for sensitivity to urban attraction.…”
Section: Calibration Prediction and Validationmentioning
confidence: 99%
“…This easily impacts the surrounding land cover and causes salinisation of the land, thus affecting the quality of the habitat and threatening the regional ecosystem. Based on the recommended values in the InVEST model guidebook and the research results of researchers worldwide in similar research areas, (Feng, Sun, & Chen, 2018; Li et al, 2018; Liu et al, 2017; Liu & Wang, 2018; Ou, Zhang, Tao, & Guo, 2018; Sharp et al, 2018; Xu, Yang, Tan, Liu, & Hu, 2018) this study determined the input parameters in model (Tables 1 and 2).…”
Section: Data Source and Research Methodsmentioning
confidence: 99%